2020
DOI: 10.31234/osf.io/7hfpx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Variability in sentence comprehension in aphasia in German

Abstract: An important property of aphasia is the variability in the performance between and within individual patients. However, there have been only a few systematic large-scale studies in a range of syntactic constructions and tasks that make it possible to investigate variability and to evaluate the quantitative predictions of competing models of sentence comprehension in aphasia (Lissón et al., under review). This is the first comprehensive investigation of variability in sentence comprehension in German, testing 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 52 publications
4
29
0
Order By: Relevance
“…One way to assess whether these deficits are plausible under a direct-access model is the computational modeling of experimental data. Lissón et al (2021) tested the direct-access model against self-paced listening data from individuals with aphasia, finding the model to be in line with multiple theories of processing deficits in aphasia. Despite this encouraging result, the model could not fit slow incorrect responses, due to its assumptions about backtrack-ing and its consequences.…”
Section: Sentence Comprehension In Aphasiamentioning
confidence: 97%
See 2 more Smart Citations
“…One way to assess whether these deficits are plausible under a direct-access model is the computational modeling of experimental data. Lissón et al (2021) tested the direct-access model against self-paced listening data from individuals with aphasia, finding the model to be in line with multiple theories of processing deficits in aphasia. Despite this encouraging result, the model could not fit slow incorrect responses, due to its assumptions about backtrack-ing and its consequences.…”
Section: Sentence Comprehension In Aphasiamentioning
confidence: 97%
“…Finally, Caplan et al (2013) claim that IWA suffer from intermittent deficiencies in their parsing system that lead to parsing failures. Previous computational modeling work has shown that these theories may be complementary (Patil et al, 2016;Lissón et al, 2021), and that IWA may experience a combination of all of these deficits (Mätzig et al, 2018).…”
Section: Sentence Comprehension In Aphasiamentioning
confidence: 99%
See 1 more Smart Citation
“…This would allow for a more comprehensive evaluation of the differences between the models, as well as an assessment of their predictive ability when modeling interference effects in different tasks, languages, and conditions. We are currently compiling a comprehensive database containing several tasks and conditions of data from IWAs and unimpaired controls in (Pregla, Lissón, Vasishth, Burchert, & Stadie, 2020). In future work, we intend to use this database to further evaluate the models discussed here.…”
Section: Some Limitations Of the Present Work And Future Directionsmentioning
confidence: 99%
“…This would allow for a more comprehensive evaluation of the differences between the models, as well as an assessment of their predictive ability when modeling interference effects in different tasks, languages, and conditions. We are currently compiling a comprehensive database containing several tasks and conditions of data from IWAs and unimpaired controls in German (Pregla et al, 2020). In future work, we intend to use this database to further evaluate the models discussed here.…”
Section: Some Limitations Of the Present Work And Future Directionsmentioning
confidence: 99%